ASUHAN GIZI KANKER PAYUDARA PASKA OPERASI - Zaki, Ibnu (JURNAL RISET GIZI, 2022)
Background : Cancer is the second leading cause of death globally. The type of cancer with the highest prevalence in women is dominated by breast cancer. Decreased appetite is a nutritional problem that occurs in cancer patients. Therefore, the intake of energy, protein, fat, and carbohydrates needs to be specifically considered. Energy, protein, fat, and carbohydrates have an important role in maintaining the nutritional status of patients to remain in the normal range, considering that there will be changes in metabolism in cancer patients which have an impact on decreasing nutritional status.Objectives : To describe the implementation of nutritional care process in breast cancer patients.Method : The study design used was a Case StudyResults : The abstract should be typed as concise as possible and should be composed of: problem statement, method, scientific finding results, and short conclusion. The abstract should only be typed in one paragraph and one-column format. (Times New Roman 12pt)Nutrition care process for cancer patients begins with nutrition screening, nutritional assessment, nutritional diagnosis, intervention, monitoring and evaluation of nutrition. Provision of a high-energy, high-protein diet for three days in the form of soft foods. Nutrition education and counseling were provided to patients and their families. Overall there was an increase in the amount of food intake every day.Conclusion : Implementation of the nutrition care process for three days increased food intake. Clinical physical data showed fluctuating results.